Social Participation and the Prevention of Functional Disability in Older Japanese: The JAGES Cohort Study - Kanamori, Satoru; Kai, Yuko; Aida, Jun; Kondo, Katsunori; Kawachi, Ichiro; Hirai, Hiroshi; Shirai, Kokoro; Ishikawa, Yoshiki; Suzuki, Kayo (PloS one, 2014)
We examined the relationship between incident functional disability and social participation from the perspective of number of types of organizations participated in and type of social participation in a prospective cohort study. The study was based on the Aichi Gerontological Evaluation Study (AGES) Cohort Study data. We followed 13,310 individuals aged 65 years or older for 4 years. Analysis was carried out on 12,951 subjects, excluding 359 people whose information on age or sex was missing. Social participation was categorized into 8 types. Compared to those that did not participate in any organizations, the hazard ratio (HR) was 0.83 (95% CI: 0.73-0.95) for participation in one, 0.72 (0.61-0.85) for participation in two, and 0.57 (0.46-0.70) for participation in three or more different types of organizations. In multivariable adjusted models, participation in the following types of organization was protective for incident disability: local community organizations (HR = 0.85, 95% CI: 0.76-0.96), hobby organizations (HR = 0.75, 95% CI: 0.64-0.87), and sports organizations (HR = 0.64, 95% CI: 0.54-0.81). Social participation may decrease the risk of incident functional disability in older people in Japan. This effect may be strengthened by participation in a variety of different types of organizations. Participating in a local community, hobby, or sports group or organization may be especially effective for decreasing the risk of disability.